2014
DOI: 10.1074/jbc.m113.539411
|View full text |Cite|
|
Sign up to set email alerts
|

Endocytosis and Vacuolar Degradation of the Yeast Cell Surface Glucose Sensors Rgt2 and Snf3

Abstract: Background:In yeast, glucose is sensed by two cell surface glucose sensors. Results: The glucose sensors are down-regulated by ubiquitination and degradation. Conclusion: The stability of the glucose sensors may be associated with their ability to sense glucose. Significance: Differential regulation of the abundance of glucose sensors enables yeast cells to respond rapidly to changing glucose levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…However, inhibition of glycolysis did not further affect Rag4 or Rgt2 localization when cells were grown in the presence of glycerol or galactose. Our finding showing that Rag4 and Rgt2 localizations are controlled by the carbon source is in agreement with a recent report showing that the stability of Snf3 and Rgt2 glucose sensors in S. cerevisiae is regulated by the concentration of extracellular glucose (33). Hence, Snf3 and Rgt2 are stabilized at the plasma membrane when the extracellular glucose concentration is in the range of their respective affinities.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, inhibition of glycolysis did not further affect Rag4 or Rgt2 localization when cells were grown in the presence of glycerol or galactose. Our finding showing that Rag4 and Rgt2 localizations are controlled by the carbon source is in agreement with a recent report showing that the stability of Snf3 and Rgt2 glucose sensors in S. cerevisiae is regulated by the concentration of extracellular glucose (33). Hence, Snf3 and Rgt2 are stabilized at the plasma membrane when the extracellular glucose concentration is in the range of their respective affinities.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, our observations that both Rag4 and Rgt2 are not stable in glucose-grown cells when the level of glycolysis is reduced suggest that the intracellular glycolytic signal may overcome the effect of extracellular glucose binding to the glucose sensors. Finally, Roy and Kim further suggest that Rgt2 stability is controlled via Rsp5-dependent ubiquitination of two lysine residues located in the Rgt2 C-terminal cytosolic extension, a region characteristic of the glucose sensors of yeasts (8,19,(33)(34)(35). Sequence alignment and computational analysis of these C-terminal extensions revealed that the two lysines important for Rgt2 stability are not conserved in Rag4 (our unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The Rgt2 high-affinity glucose sensor is stabilized by glucose and is degraded in the absence of glucose through its ubiquitination and consequent targeting to the vacuole (Roy and Kim, 2014), and Yck-dependent phosphorylation of the uracil permease Fur4 within a PEST sequence stimulates its ubiquitination and degradation (Marchal et al , 2000). The C-terminal region of Rgt2 near box1, where Yck-dependent phosphorylation occurs, resembles a PEST sequence that we surmised could function to regulate the stability of Rgt2.…”
Section: Resultsmentioning
confidence: 99%
“…Knowing that the Ycks are required for stability of several membrane proteins, including transporters and permeases, and that Rgt2 and Snf3 are turned over in response to low and high glucose levels, respectively (Roy and Kim, 2014), we were surprised to find that Rgt2 is stable in a yck1∆yck2 ts mutant and that mutation of the Yck-dependent phosphorylation sites of Rgt2 does not affect its stability (even though the phosphorylation sites on Rgt2 are in a region that resembles a PEST degradation sequence).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation